2008
DOI: 10.1186/1749-799x-3-47
|View full text |Cite
|
Sign up to set email alerts
|

Pre-surgical radiologic identification of peri-prosthetic osteolytic lesions around TKRs: a pre-clinical investigation of diagnostic accuracy

Abstract: Background: Emerging longitudinal data appear to demonstrate an alarming trend towards an increasing prevalence of osteolysis-induced mechanical failure, following total knee replacement (TKR). Even with high-quality multi-plane X-rays, accurate pre-surgical evaluation of osteolytic lesions is often difficult. This is likely to have an impact on surgical management and provides reasonable indication for the development of a model allowing more reliable lesion assessment. The aim of this study, using a simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…A total of 37 bone lesions were drilled at defined distances (4, 6, or 10 mm) to the screw axis using a custom‐made polyethylene drill guide, imitating osteolytic lesions and lucencies as found in vivo . Lesions were distributed over two defined observation areas around each screw as outlined in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 37 bone lesions were drilled at defined distances (4, 6, or 10 mm) to the screw axis using a custom‐made polyethylene drill guide, imitating osteolytic lesions and lucencies as found in vivo . Lesions were distributed over two defined observation areas around each screw as outlined in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Postoperative care of TKAs usually includes periodic physical examinations, as well as radiographic follow-up [ 17 ]. In the presence of abnormal findings in postoperative follow-up examinations, e.g., suspicious loosening or osteolytic lesions, further work-up includes scintigraphy [ 20 ] and computed tomography (CT) [ 10 , 19 ]. The latter provides excellent spatial resolution of the bones, soft-tissue, and prosthetic material, but it has some limitations due to metal artifacts at the bone/prosthesis interface [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…with single-photon emission computed tomography (SPECT/CT) assessments, in which a sensitivity for loosening of 86.6% for femoral and 93.3% for tibial components were reported (29). Good to very good sensitivity and specificity of identification of periprosthetic osteolysis have been reported in ex vivo human cadaveric and pig bone models (1416) in regard to the presence or absence of osteolytic lesions. In our study, we graded the size and location of osteolysis by two validated classification systems (AORI, Clatworthy and Gross) (25).…”
Section: Discussionmentioning
confidence: 98%
“…Revision surgery for component malrotation, as detected by CT, has been reported to be as beneficial for the patient as a revision for the indication of aseptic loosening (13). Most studies that have examined osteolysis or aseptic loosening with conventional CT scans for TKA have been performed ex vivo (14)(15)(16). Hirschmann et al showed that SPECT/ CT could be used to detect aseptic loosening (17).…”
Section: Introductionmentioning
confidence: 99%